Dopamine-dependent periadolescent maturation of corticostriatal functional connectivity in mouse - Galiñanes, Gregorio Luis (2009)
Altered corticostriatal information processing associated with early dopamine systems dysfunction may contribute to attention deficit/hyperactivity disorder (ADHD). Mice with neonatal dopamine-depleting lesions exhibit hyperactivity that wanes after puberty and is reduced by psychostimulants, reminiscent of some aspects of ADHD. To assess whether the maturation of corticostriatal functional connectivity is altered by early dopamine depletion, we examined preadolescent and postadolescent urethane-anesthetized mice with or without dopamine-depleting lesions. Specifically, we assessed (1) synchronization between striatal neuron discharges and oscillations in frontal cortex field potentials and (2) striatal neuron responses to frontal cortex stimulation. In adult control mice striatal neurons were less spontaneously active, less responsive to cortical stimulation, and more temporally tuned to cortical rhythms than in infants. Striatal neurons from hyperlocomotor mice required more current to respond to cortical input and were less phase locked to ongoing oscillations, resulting in fewer neurons responding to refined cortical commands. By adulthood some electrophysiological deficits waned together with hyperlocomotion, but striatal spontaneous activity remained substantially elevated. Moreover, dopamine-depleted animals showing normal locomotor scores exhibited normal corticostriatal synchronization, suggesting that the lesion allows, but is not sufficient, for the emergence of corticostriatal changes and hyperactivity. Although amphetamine normalized corticostriatal tuning in hyperlocomotor mice, it reduced horizontal activity in dopamine-depleted animals regardless of their locomotor phenotype, suggesting that amphetamine modified locomotion through a parallel mechanism, rather than that modified by dopamine depletion. In summary, functional maturation of striatal activity continues after infancy, and early dopamine depletion delays the maturation of core functional capacities of the corticostriatal system.